How brand ambassador and trust on consumer purchase decisions of fashion products in the digital era - Dede Suleman; Yohanes Totok Suyoto; Teguh Prasetio (Journal of Economics and Business Letters, 2022)
One of the changes happening in the current new world era is the phenomenon of brand ambassadors, which are one of the determinants of what consumers want to buy. With today's advancements in digital technology, do consumers care more about who the model is for a product, and if they increase their trust in that model, will a purchase necessarily happen? The purpose of this research is to examine the effect of brand ambassador and trust variables on consumer shopping decisions. In this study, the researcher used three variables, ten dimensions where each dimension was represented by two indicators so that in this study there were twenty indicators, which would later be changed in the form of questions to respondents. The population used is consumers who have shopped for fashion products using brand ambassadors. Given that the population is very large, the researchers used quota sampling to determine the number of samples. The study used 5 times the number of indicators, so a sample of 100 respondents was processed through the Structural Equation Modeling analysis technique of AMOS software. The results of data processing show that brand ambassadors and trust significantly influence consumers' purchasing decisions.